Clinical learning evaluation among undergraduate physical therapy students during rotations in teaching hospitals of Sialkot and Lahore - Arif, Gulafshan; Saleem, Zunaira; Asif, Rimsha; Yousaf, Qandeel (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the clinical learning environment among undergraduate physical therapy students. Method: The descriptive, cross-sectional study was conducted from January 23 to May 25, 2023, after approval from the ethics review committee of Imran Idrees Institute of Rehabilitation Sciences, Sialkot, Pakistan, and comprised undergraduate physical therapy students of either gender aged 19-26 years in their 3rd to 5th academic year studying in different institutions in Lahore and Sialkot. Data was collected using the clinical learning evaluation questionnaire. Data was analysed using SPSS 22. Results: Of the 295 students, 269(91.2%) were females and 26(8.8%) were males. The overall mean age was 22.03±1.14 years. There were 210(71.2%) students enrolled in the semester system, while 85(28.8%) were part of the annual system. The overall mean score was 71.05±10.20. Supervision (76.02±11.80) and motivation (80.21± 11.71) were the most satisfying part of clinical learning identified by the students. Conclusion: The clinical learning environment demonstrated high satisfaction levels in supervision and motivation domains, while improvements were needed in the areas of cases, authenticity and organisation of doctor-patient encounters. Key Words: Environment, Learning, Motivation, Physical therapy, Students, Supervision, Undergraduate.